KAJIAN PENGARUH BERAT BIJI KAKAO PERKOTAK DAN WAKTU PENGADUKAN TERHADAP KEBERHASILAN PROSES FERMENTASI - Sabahannur, St.; Nirwana, Nirwana (Universitas Tanjungpura, 2017)
This study aim to influence seed weight per box of fermentation and stirring time on the success of the fermentation process. Research using a randomized block design with two factors. The first factor seed weight per box consists of: 15 kg, 20 kg and 25 kg. The second factor, while stirring during fermentation: stirring during 48 hours (1 time), and a stirring time of 48, 72, and 96 hours (3 times) fermentation. The results showed fermentation of cocoa beans each 15 kg, 20 kg and 25 kg has no effect on changes in temperature, pH, total acid and fermentation index. The highest temperature during fermentation at 44-45oC, while stirring time (aeration) significantly affects the pH, fermentation index and slaty beans. Stirring 3 times better than one times in terms of pH (5.6), fermentation index of 1.62 and 3.4% slaty beans.Keywords: fermentation, seed weight, stirring, index fermentation